Age and growth of the highly exploited narrownose smooth-hound (Mustelus schmitti) (Pisces: Elasmobranchii) - Molina, Juan Manuel (2017)
The narrownose smoothhound (Mustelus schmitti) is the most exploited elasmobranch of Argentina, Brazil, and Uruguay and is considered endangered (IUCN Red List of Threatened Species). Providing information on age and growth can improve efforts for conservation of this species. Therefore, our objective was to provide accurate estimates of the age structure and growth parameters for narrownose smooth-hound from Anegada Bay, an important shark nursery area in Argentina. In vertebrae of narrownose smooth-hound, we observed a pattern of alternating opaque and translucent bands and a yearly periodicity in the deposition of this pattern. Ages determined from vertebral band counts ranged from 0 to 11 years. Calculated longevity and total natural mortality rates were 20.87 years and 0.19/year for females and 12.24 years and 0.26/year for males, respectively. This species reached a size of approximately 400 mm in total length in the initial year of growth, and the age at first maturity was 7.61 years for females and 6.79 years for males. The slow growth and late age at maturity of the narrownose smoothhound indicate a need for additional conservation measures to rebuild the population and achieve a sustainable fishery in the 3 countries in which it is distributed.